1985
DOI: 10.5006/1.3582016
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Surface Additives on the Oxidation of Chromia-Forming Alloys

Abstract: The influence of the surface application of active elements on the composition, morphology, adherence, and growth rate of oxide scales formed during high temperature exposure has been investigated. The active elements were applied as aqueous solutions of nitrate salts that were subsequently transformed into oxide. The active elements used were: Y, Ce, La, Hf, Ca, and Zr. The chromia-forming substrates used were AISI 304 and 310 stainless steels and IN 738, a nickel base alloy. To determine the effect of the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(48 citation statements)
references
References 3 publications
2
42
0
Order By: Relevance
“…Other authors pointed out that Mn 1.5 Cr 1.5 O 4 located at the external interface, could reduce the conversion of Cr 2 O 3 into a CrO 3 volatile oxide above 900 8C [29][30][31]. Some authors indicated that Mn 1.5 Cr 1.5 O 4 is nonprotective because it presents a porous structure [32,33]. Nevertheless, if manganese oxides crack at the external interface it does not affect the adherent protective chromia scale [34].…”
Section: Manganese Influencementioning
confidence: 99%
See 1 more Smart Citation
“…Other authors pointed out that Mn 1.5 Cr 1.5 O 4 located at the external interface, could reduce the conversion of Cr 2 O 3 into a CrO 3 volatile oxide above 900 8C [29][30][31]. Some authors indicated that Mn 1.5 Cr 1.5 O 4 is nonprotective because it presents a porous structure [32,33]. Nevertheless, if manganese oxides crack at the external interface it does not affect the adherent protective chromia scale [34].…”
Section: Manganese Influencementioning
confidence: 99%
“…Then the silica phase leads to a decrease in the alloy oxidation rate [40]. The high oxygen affinity of silicon, permit its internal oxidation, developing SiO 2 precipitates at the internal interface [32,41]. Then, silica acts as a diffusion barrier and leads to peg the chromia scale on the substrate [42,43].…”
Section: Silicon Influence On High Temperature Oxidationmentioning
confidence: 99%
“…Small amounts (usually below 1%) of reactive elements (Sc, Ti, Y, Zr, Ce, La, ect.) clearly improve the oxidation behaviour of chromia-and alumina-forming alloys [6][7]. Several explanations are given about this effect, usually called reactive element effect (REE), namely a modification of the diffusion mechanisms, a reduction of vacancies condensation at the internal interface, a formation of reactive element oxide inclusions trapping alloy impurities [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…An attractive way to overcome these problems while saving expensive and scarce metals like nickel is surface coating. From simple hot-dipping procedures 3 to sputtering, 4 chemical vapour deposition (CVD) 5 or ion implantation, 6 - number of processes described in the literature covers the whole set of known surface coating techniques, but most of them result either in inhomogeneous coatings or are costly enough to prevent their use in industrial applications.…”
Section: Introductionmentioning
confidence: 99%